Antagonistic Activity of Chilean Strains of Pseudomonas protegens Against Fungi Causing Crown and Root Rot of Wheat (Triticum aestivum L.) - Castro Tapia, María Paz; Madariaga Burrows, Ricardo P.; Ruiz Sepúlveda, Braulio; Vargas Concha, Marisol; Vera Palma, Carola; Moya-Elizondo, Ernesto A. (Frontiers in Plant Science, 2020)
Seed treatments with antagonistic bacteria could reduce the severity of crown and root rot diseases in wheat crops. The objective of this study was to evaluate the potential antagonistic activity of a bacterial consortium of three Chilean strains of Pseudomonas protegens against the wheat crown and root rot pathogens Gaeumannomyces graminis var. tritici, Rhizoctonia cerealis, and Fusarium culmorum. Two field experiments were carried out on artificially infested soil during two consecutive seasons (2016-2017 and 2017-2018) in an Andisol soil of southern Chile. Control treatments (not inoculated with fungi) were also included. Each treatment included a seed treatment of spring wheat cv. Pantera-INIA with and without the bacterial consortium. Both phytosanitary damage (incidence and severity) and agronomic components were evaluated. Bacterial populations with the phlD+ gene in the wheat plant rhizosphere during anthesis state (Z6) were also quantified. In both seasons, infection severity decreased by an average of 16.8% in seeds treated with P. protegens consortium, while yield components such as spikes m-1 and number of grains per spike increased. The use of antagonistic bacteria resulted in a total yield increase only during the first experimental season (P < 0.05). In general, accumulated rainfall influenced the antagonistic effect of the consortium of P. protegens strains, accounting for the differences observed between the two seasons. The results suggest that this P. protegens consortium applied on seeds can promote plant growth and protect wheat crops against crown and root rot pathogens in Southern Chile under field conditions.